Climatology of Tehran surface heat Island: a satellite-based spatial analysis - Motahhareh Zargari; Abbas Mofidi; Alireza Entezari; Mohammad Baaghideh (Scientific Reports)
Abstract With a population nearing 15 million, the metropolitan area of Tehran faces numerous environmental challenges due to inadequate urban strategies and hasty, ineffective planning. The primary objective of this research is to investigate the Urban Heat Island (UHI) climatology in the metropolis of Tehran. To achieve this, daily Land Surface Temperature (LST) data from the MODIS-Aqua, with a spatial resolution of 1 km, was utilized over a 19-year period (2003–2021). This study delves into various climatic characteristics, including the urban-rural temperature difference, urban heat hotspots, the structure of the Surface Urban Heat Island (SUHI), trends in LST changes, and the roles of elevation and vegetation cover in the spatial distribution of LST, at both monthly and annual scales. Findings reveal that, compared to daytime Aqua-MODIS LST data, nighttime data provides a more reliable means of detecting and studying the SUHI in Tehran throughout the year. Additionally, the employment of nighttime data significantly reduces seasonal variations and month-to-month fluctuations in the temperature difference between the urban warm core and surrounding areas in Tehran. A climatological analysis of nighttime LST revealed a mean annual temperature difference of 6.17 °C between Tehran and its surrounding suburbs. This difference fluctuated monthly, ranging from a minimum of 5.73 °C in November to a maximum of 6.49 °C in September. Overall, the smallest temperature differences occurred during autumn and spring, while the largest differences were observed in summer. However, autumn and summer exhibited the greatest and least interannual variability, respectively. Furthermore, over the 19-year period, the annual temperature difference between the urban and suburban areas ranged from a minimum of 5.09 °C (2020) to a maximum of 6.70 °C (2008). The SUHI analysis suggests that Tehran, due to its surrounding mountainous terrain and numerous suburban developments, does not exhibit a classic UHI with a pronounced temperature difference. Moreover, the results indicate a rising temperature trend in the city. Specifically, the second decade of the study period witnessed a notable increase in positive LST anomalies within Tehran. The analysis reveals a significant increase in Tehran’s surface temperature, with a rate of 0.74 °C per decade, amounting to a total increase of 1.48 °C. Concurrently, a discernible upward trend in the temperature differential between the urban and suburban areas has been observed over the last two decades. A comparative study of the roles of elevation and vegetation cover in LST distribution indicates that the temperature difference between the urban and suburban areas of Tehran is more closely related to elevation changes than to vegetation distribution.